Biotechnology : our future as human beings and citizens - Sutton, Sean D., 1965- (SUNY series in philosophy and biology., 2009)
An essential introduction to a controversial yet crucial field of research, Biotechnology surveys recent advances in the field and offers a wide range of opinions for and against expanding this new branch of science. Incisively examining such key topics as therapeutic cloning, genetic enhancement, stem cell therapy, and the use of psychotropic drugs such as Prozac and Ritalin, contributors to this volume agree that biotechnology will inevitably change human life. However, they debate the right way to balance the potential to cure disease and relieve human suffering with the need to respect life and preserve human dignity. Several explore the way major religions--both Eastern and Western--treat the subject. Others analyze the role of government in biotechnology and specific applications of the technology that should be practiced. Serving as an introduction to this ethically complicated and significant scientific movement, the book ultimately raises the broader, fundamental question of the meaning of human flourishing.